A Study of Mortality in Burns (A review of 1513 cases) - Sinka, Prof. R. C.; Verma, Dr. S. K. (Indian Journal of Plastic Surgery, 1980)
1. Mortality among 1513 cases of burns admitted in Patna Medical college Hospital, TUnder Plastic Surgery Department from Jan., 1970 to Dec., 1979 were reviewed.2. 60.62% of the cases were of major burns (above 30%), 14.34% were between 15% to 30% and 25.04% were below 15%.3. There was a total mortality of 498 cases out of which 213 were males and 385 were females with an overall mortality of 37.7% in males and 30.5% in females.4, 86.97% of the cases had received the burn injury due to cloth catching fire and the accident was preventable.5. 40.2%, of the cases were from the age group 12 to 45 years. 24.8%, above 45 years and 18.4 below 12 years.